2006
DOI: 10.1021/bm060715f
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Microchannelling in Dense Collagen Scaffolds by Soluble Phosphate Glass Fibers

Abstract: A problem with tissue engineering scaffolds is maintaining seeded cell viability and function due to limitations of oxygen and nutrient transfer. An approach to maintain suitable oxygen concentrations throughout the scaffold would be to controllably incorporate microchannelling within these scaffolds. This study investigated the incorporation of unidirectionally aligned soluble phosphate based glass fibers (PGF) into dense collagen scaffolds. PGF are degradable, and their degradation can be controlled through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
86
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(86 citation statements)
references
References 29 publications
0
86
0
Order By: Relevance
“…21 Our technique of plastic compression differs from earlier studies, because we use cell culture inserts with 3 mm pores to reduce the liquid content instead of nylon and stainless steel meshes. [7][8][9][10]21 Furthermore, the dimensions of our scaffolds are much larger than reported earlier and the compression times therefore longer. The latter reduces the attractivity to enrich scaffolds with cells, which should not easily survive in such large constructs.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…21 Our technique of plastic compression differs from earlier studies, because we use cell culture inserts with 3 mm pores to reduce the liquid content instead of nylon and stainless steel meshes. [7][8][9][10]21 Furthermore, the dimensions of our scaffolds are much larger than reported earlier and the compression times therefore longer. The latter reduces the attractivity to enrich scaffolds with cells, which should not easily survive in such large constructs.…”
Section: Discussionmentioning
confidence: 68%
“…The latter reduces the attractivity to enrich scaffolds with cells, which should not easily survive in such large constructs. 10 To our knowledge, a detailed rheological characterization of dense collagen I scaffolds, as in the current study, has not been reported previously in literature. With our dense collagen scaffolds, we are able to approach the viscoelastic properties of the NP, in particular its elasticity.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…largely irreversible) deformation as fl uid is forced out of the collagen fi bril network, and predictably the same plastic (non-elastic) deformation should occur at the micron scale around structures pressed into the surface. This process also leaves stable micro-channels running through the bulk of the material where embedded phosphate glass fi bres dissolve (Nazhat et al, 2007). However, the fl uid fl ow out of such gels and eventual collagen distribution during PC are by no means homogeneous (Hadjipanayi et al, 2011), and this study clearly shows that topographic patterning can be signifi cantly infl uenced by these local factors.…”
Section: T Alekseeva Et Al Scaffolds With Predictable Surface Topologymentioning
confidence: 77%
“…A concern when increasing the collagen content of the hydrogel is that diffusion of nutrients and waste products through the scaffold would not be sufficient to maintain cell viability over extended periods of time. To address this problem Nazhat et al (2007) incorporated micro-channels into the gels using soluble phosphate glass fibres and after 24 h the cell viability of encapsulated fibroblasts was seen to be greater than 80%.…”
Section: Skinmentioning
confidence: 99%